Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2217/bmm-2016-0286
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microRNA-19a as a Potential Biomarker for Esophageal Squamous cell Carcinoma Diagnosis and Prognosis

Abstract: Aim:To investigate whether plasma miR-19a can serve as a biomarker for esophageal squamous cell carcinoma (ESCC) diagnosis and prognosis. Materials & methods: Plasma samples from 89 ESCC, 45 benign lesion patients and 80 healthy controls were subjected to RT-qPCR analyses for miR-19a. In addition, plasma samples from 30 patients were collected before and after surgery for the same analyses. Results: Plasma miR-19a was significantly increased in ESCC patients compared with healthy controls. The sensitivity of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…A combination of miR‐19a and cytokeratin fragment 21‐1 (Cyfra21‐1) further improved the diagnostic profile. Moreover, plasma miR‐19a was anticipated as a potential biomarker that complements Cyfra21‐1 in early‐stage detection, cancer screening, monitoring, postoperative prognosis, and predicting the recurrence/metastasis after surgery in ESCC . The diagnostic potential of serum miR‐1297 in ESCC and its expression level was detected in patients with ESCC and HC by using qRT‐PCR, a combined RT‐PCR and quantitative real‐time polymerase chain reaction (qPCR) technique.…”
Section: Biomarkers In Oscc and Esccmentioning
confidence: 99%
“…A combination of miR‐19a and cytokeratin fragment 21‐1 (Cyfra21‐1) further improved the diagnostic profile. Moreover, plasma miR‐19a was anticipated as a potential biomarker that complements Cyfra21‐1 in early‐stage detection, cancer screening, monitoring, postoperative prognosis, and predicting the recurrence/metastasis after surgery in ESCC . The diagnostic potential of serum miR‐1297 in ESCC and its expression level was detected in patients with ESCC and HC by using qRT‐PCR, a combined RT‐PCR and quantitative real‐time polymerase chain reaction (qPCR) technique.…”
Section: Biomarkers In Oscc and Esccmentioning
confidence: 99%
“…Previous studies have shown that miRNA dysregulation is involved in the development of EC and that miRNAs act as both oncogenes and tumor suppressor genes. [16][17][18] He et al divided human EC cell lines KYSE170 and ECA109 into two groups: one cultured in RPMI 1640 medium containing 10% fetal bovine serum (FBS) and the other in RPMI 1640 medium containing 10% FBS plus 50 μM/L ZnSO 4 . The miRNA levels in the two cell lines were then measured to analyze the influence of the Zn level on the miRNAs.…”
Section: Zn Deficiency Affects the Development Of Ec By Regulating MImentioning
confidence: 99%
“…Micro‐RNAs (miRNAs, miRs) are non‐coding RNAs approximately 18–22 nucleotides in length that post‐transcriptionally regulate gene expression by base‐pairing to partially complementary sequences in the 3′‐untranslated region (UTR) of their target messenger RNA (mRNA). Previous studies have shown that miRNA dysregulation is involved in the development of EC and that miRNAs act as both oncogenes and tumor suppressor genes …”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer (EC) is one of the most malignant types of tumor in humans (1)(2)(3)(4). As the eighth most common type of cancer worldwide, the yearly estimated number of new EC cases in the USA alone is >16,000, with an estimated >150,000 cases of EC-associated mortality each year (1)(2)(3)(4). Histologically, as the two major subtypes of EC, esophageal adenocarcinoma and esophageal squamous carcinoma (ESCC) represent ~90% of all EC cases (1,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…As the eighth most common type of cancer worldwide, the yearly estimated number of new EC cases in the USA alone is >16,000, with an estimated >150,000 cases of EC-associated mortality each year (1)(2)(3)(4). Histologically, as the two major subtypes of EC, esophageal adenocarcinoma and esophageal squamous carcinoma (ESCC) represent ~90% of all EC cases (1,(5)(6)(7). Among them, ESCC is the most dominant subtype in developing countries, including China (8,9).…”
Section: Introductionmentioning
confidence: 99%